NORTH AMERICAN DROUGHTS OF THE MID TO LATE NINETEENTH CENTURY: A HISTORY, SIMULATION AND IMPLICATION FOR MEDIAEVAL DROUGHT - Herweijer C.; Seager R.; Cook E.R. (My University, 2006)
Unlike the major droughts of the twentieth century that are readily identified in the instrumental record, similar events in the nineteenth century have to be identified using a combination of proxy data, historical accounts and a sparse collection of early instrumental records. In the USA, three distinct periods of widespread and persistent drought stand out in these records for the latter half of the nineteenth century: 1856-1865, 1870-1877 and 1890-1896. Each of these events is shown to coincide with the existence of an anomalously cool, La Nifia-like tropical Pacific. To examine the physical mechanisms behind these droughts two ensembles of simulations with an atmosphere general circulation model (AGCM) were generated: the first forces an AGCM with the observed history of Sea Surface Temperatures (SSTs) everywhere from 1856 to 2001 (the GOGA experiment), the second forces the AGCM only with tropical Pacific SSTs, being coupled to a two-layer entraining mixed layer (ML) ocean elsewhere (the POGA-ML experiment). Owing to a sparsity of instrumental precipitation data at this time, proxy evidence from tree rings is used as verification. A comparison of modelled soil moisture with tree-ring reconstructions of the Palmer Drought Severity Index (PDSI), a proxy for soil moisture, from the North American Drought Atlas is made. Both the POGA-ML and GOGA ensemble means capture the three multi-year droughts of the mid to late nineteenth century, indicating that the droughts were SST forced. The similarity of the POGA-ML and GOGA simulations implies that the component of each drought signal that is forced by the SST is driven ultimately by the La Nifia-like tropical Pacific. The global atmosphere-ocean context of each of the mid to late-nineteenth century droughts reveals a zonally and hemispherically symmetric pattern consistent with forcing from the tropics. In addition, Rossby wave propagation from the cooler equatorial Pacific amplifies dry conditions over the USA. Finally, using published coral data for the last millennium to reconstruct a NINO 3.4 history, the modern-day relationship between NINO 3.4 and North American drought is applied to recreate two of the severest Mediaeval ‘drought epochs’ in the western USA. The large-scale spatial similarity to the Drought Atlas data demonstrates the potential link between a colder eastern equatorial Pacific and the persistent North American droughts of the Mediaeval period.
Keywords: DROUGHT; LA NINA; NORTH AMERICA; MEGADROUGHT; MEDIAEVAL CLIMATE ANOMALY